Regulating cognitive control through approach-avoidance motor actions - Koch, Severine; Holland, Rob W.; van Knippenberg, Ad (Cognition, 2008)
In two studies, the regulatory function of approach-avoidance cues in activating cognitive control processes was investigated. It was hypothesized that avoidance motor actions, relative to approach motor actions, increase the recruitment of cognitive resources, resulting in better performance on tasks that draw on these capacities. In Study 1, error rates on a verbal response mode version of the Stroop task were analyzed. On inconsistent Stroop trials, participants in the avoidance condition made significantly fewer errors than those in the approach condition. In Study 2, performance differences on a task switching paradigm were investigated. Crucially, approach and avoidance motor actions were manipulated within-subjects by alternating between approach and avoidance motor actions on 4 blocks of trials. Temporal switching costs were significantly lower while performing an avoidance, compared to an approach motor action. These results support our hypothesis that avoidance cues, relative to approach cues, lead to improved performance on cognitive control tasks.